2016
DOI: 10.1103/physrevb.94.201119
|View full text |Cite
|
Sign up to set email alerts
|

Tracking local magnetic dynamics via high-energy charge excitations in a relativistic Mott insulator

Abstract: We use time-and energy-resolved optical spectroscopy to investigate the coupling of electron-hole excitations to the magnetic environment in the relativistic Mott insulator Na2IrO3. We show that, on the picosecond timescale, the photoinjected electron-hole pairs delocalize on the hexagons of the Ir lattice via the formation of quasi-molecular orbital (QMO) excitations and the exchange of energy with the short-range-ordered zig-zag magnetic background. The possibility of mapping the magnetic dynamics, which is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For these materials the large spin-orbit interaction leads to a sizeable bond directional spin exchange, whereas the symmetric Heisenberg exchange cancels out by virtue of the edge-sharing octahedra geometry, making them promising candidates for Kitaev physics [12][13][14] . Still, the remaining Heisenberg interaction, present due to small structural distortions away from the ideal honeycomb structure, 15 is an adversary to spin liquid formation, and generally favors a spin-ordered ground state 13,16,17 . By modulating spin entropy through finite temperature effects 18,19 or by adding external magnetic fields 20 , one can however stabilize proximate or fieldinduced spin liquid phases at thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…For these materials the large spin-orbit interaction leads to a sizeable bond directional spin exchange, whereas the symmetric Heisenberg exchange cancels out by virtue of the edge-sharing octahedra geometry, making them promising candidates for Kitaev physics [12][13][14] . Still, the remaining Heisenberg interaction, present due to small structural distortions away from the ideal honeycomb structure, 15 is an adversary to spin liquid formation, and generally favors a spin-ordered ground state 13,16,17 . By modulating spin entropy through finite temperature effects 18,19 or by adding external magnetic fields 20 , one can however stabilize proximate or fieldinduced spin liquid phases at thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…It has further been shown that the geometric frustration plays an important role in the physics of non-Fermi liquid of doped Mott insulators and high-Tc superconductors [2][3][4][5][6] . Typically, frustrated magnetic systems show extensive degeneracy of their ground states in the classical limit, which can be lifted by addition of thermal or quantum fluctuations, or perturbations such as spin-orbit interactions, spin-lattice couplings, further neglected exchange terms and impurities.…”
Section: Introductionmentioning
confidence: 99%
“…These materials undergo an antiferromagnetic phase transition at a Néel temperature T N , whereas, above T N , maintain short range magnetic correlations up to a temperature T corr T N . For instance, Na 2 IrO 3 undergoes a zig-zag magnetic transition at T N =15 K , while short range correlations are retained at temparetures as high as T corr ∼100 K [58,59]. The characteristic L is now dictated by the spin-spin correlation length.…”
Section: Applications To Real Materials: Case Studiesmentioning
confidence: 99%